Gestión administrativa y su relación con el desempeño laboral de los colaboradores de la panadería Carley Iquitos, 2023 - Fernández Mestanza, Yolanda Isabel (2023)
The purpose of this study is to analyze the connection between management in administration and the work performance of employees at Carley Bakery, located in Iquitos in 2023, was the aim of this research. The approach used was descriptive and quantitative, with a non-experimental design. In descriptive studies, the main purpose is to define attributes and peculiarities of concepts, phenomena, variables, or events in a specific context. The results led to the deduction that there is a highly positive correlation between the two variables analyzed, evidenced by a Pearson coefficient of 0.869**, and a bilateral significance value of 0.000.